Functionalized Carbon Quantum Dots from Rice Husks as Nanofiller in Membrane System - ZAINAL ABIDIN, NUR HAFIZAH (2021)
The incorporation of inorganic nanofillers in thin film composite (TFC) has shown potential to improve membrane performance in water filtration. Nanofillers were used to enhance the properties of membrane. However, most fillers embedded in the PA layer of membrane are in larger sizes (~100 nm), thus tend to form agglomerates. Therefore, in this study, carbon quantum dots (CQDs) synthesized from rice husks and further functionalized with carboxyl and amino groups, each denoted as CCQDs and NCQDs with loading ranging from 0.1 to 0.3 wt% was embedded as nanofillers in membrane. High-Resolution Transmission Electron Microscopy (HRTEM) shows that CQDs are in the size ranges of less than 10 nm, significantly smaller than other conventional nanoparticles. Fourier-Transform Infrared Spectroscopy (FTIR) results show that CQDs possess oxygen-containing groups that assist in hydrogen bonding. Thin Film Nanocomposite (TFN) membrane was prepared through interfacial polymerization technique between piperazine (PIP) and trimesoyl chloride (TMC) solutions. The process involved fabrication of TFN membrane on the support membrane with CCDQS and NCQDs as aqueous additives. The membrane substrate was initially immersed in aqueous solution containing 2% (w/v) PIP together with functionalized CQDs. The membrane support was then dipped into the organic solution containing n-heptane with 0.15% (w/v) of TMC for about 2 minutes. Contact angle result shows that the hydrophilicity of membrane was significantly enhanced by the incorporation of CQDs. The contact angle of membrane decreases in the order of PSf > TFC > TFN (CQDs) > TFN (NCQDs) > TFN (CCQDs). The dense structure of membrane also changes with the presence of CQDs where its roughness increases. At 6 bar feed pressure in dead-end nanofiltration setup, the membranes with 0.2 wt% of CQDs exhibited permeate flux of more than 30 L/m2.hr which was superior to that of pristine TFC membrane with only 15 L/m2.hr. To add, the salt rejection could be maintained at more than 90%. To conclude, the improved performance indicates that CQDs are worth to be explored as nanofillers.